(untitled) (Research, Society and Development, 2020)
The present study aimed to obtain the sweet potato flour through the spray drying process, in a spouted bed and to evaluate the effect of the temperatures used on its physical-chemical properties. The sweet potato was submitted to the spouting bed drying process at temperatures of 50, 60 and 70 °C, air flow in the atomizing nozzle of 3.0 m3/min and pump flow rate of 2.7 ml/min. The fresh sweet potatoes and the flours obtained were characterized according to the following physical-chemical parameters: humidity, total solids, water activity (aw), ash, lipids, carbohydrates, pH, total tileable acidity (ATT), total soluble solids (SST) and ratio (SST/ATT ash when there was an increase in the drying temperature. The drying allowed a reduction in the moisture content, water activity of fresh sweet potatoes, guaranteeing a longer shelf life of the product. There was). The sweet potato in natura showed a high moisture content of 69.48% and an increase in the contents of statistically significant differences between the temperatures used in relation to the physical-chemical parameters. However, the temperature of 80 °C enabled the highest value of total soluble solids, ratio (SST/ATT) and total carbohydrates, showing the technological potential of the powder product.